A case of primary rectal teratoma - Aikepaer Aiken; Wen Yu; Aini Abudoureyimu; Xuelaiti Aizimu; Jinlu Tong (Turkish Journal of Gastroenterology, 2020)
Cite this article as: Aiken A. Yu W, Abudoureyimu A. Aizimu X. Tong J. A case of primary rectal teratoma. Turk J Gastroenterol 2020; 31(11): 835-7.